2022
DOI: 10.1111/1744-7941.12355
|View full text |Cite
|
Sign up to set email alerts
|

Work, life and COVID‐19: a rapid review and practical recommendations for the post‐pandemic workplace

Abstract: Remote working because of the COVID‐19 pandemic has eroded boundaries between work and home, necessitating the need to evaluate the long‐term impacts of these changes and mitigate any negative effects on workers' work‐life experiences. To do so, we reviewed and examined work‐life research published since the start of the pandemic. The review yielded a sample of 303 work‐life scholarly articles, with three common themes: 1) work‐life boundaries have become more permeable, with behavior‐based and time‐based work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 76 publications
0
22
0
Order By: Relevance
“…Indeed, the pandemic introduced a myriad of sources of job-related stress, including layoffs, reduced income, reduced job security and, for remote workers, a diminished ability to ‘leave work at work’ 30. For in-person and essential workers, the pandemic led to lengthy work schedules, minimal time off, diminished time to engage in coping and stress-relieving strategies that had not yet been impacted by the pandemic, increased burnout, and increased susceptibility to the COVID-19 virus 31. Previous literature has found that increased stress and anxiety about employment and finances is associated with greater nicotine consumption 32.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the pandemic introduced a myriad of sources of job-related stress, including layoffs, reduced income, reduced job security and, for remote workers, a diminished ability to ‘leave work at work’ 30. For in-person and essential workers, the pandemic led to lengthy work schedules, minimal time off, diminished time to engage in coping and stress-relieving strategies that had not yet been impacted by the pandemic, increased burnout, and increased susceptibility to the COVID-19 virus 31. Previous literature has found that increased stress and anxiety about employment and finances is associated with greater nicotine consumption 32.…”
Section: Discussionmentioning
confidence: 99%
“…HRM practices are important to employees' work-family outcomes (Batt and Valcour 2003;Wattoo, Zhao and Xi 2020). Various empirical studies have explored the role of work-to-family conflict (Chan et al 2022). These research findings indicate that support at work and home (Nasurdin and Hsia 2008), job schedule demands (Lingard and Francis 2005), work overload and parenting stress (Hong, Liu and Zhang 2021), after-hours work-related technology use, role overload, and job autonomy (Andrade and Petiz Lousã 2021) can be used to predict work-to-family conflict.…”
Section: Digital-oriented Training Pos and Work-to-family Conflictmentioning
confidence: 99%
“…Work-to-family conflict can be caused by employees' work and family role incompatibility, such as work issues taking precedence over family issues or vice versa (Frone 2000;Dousin, Collins and Kler 2022). Prior studies have explored the negative impact of work-to-family conflict on employees (Chan et al 2022). HRM policies aimed to ease work-to-family conflict could help employees avoid adverse health outcomes (e.g.…”
Section: Digital-oriented Training Pos and Work-to-family Conflictmentioning
confidence: 99%
See 1 more Smart Citation
“…This is evidenced by lower scores on tests of language and motor skills ( Wenner Moyer, 2022 ), while the consequences of school closures may lead to lifetime welfare losses of children ( Fuchs-Schündeln, Krueger, Ludwig, & Popova, 2022 ). Additionally, the shift to remote working came with both opportunities, such as enhanced productivity and flexibility, and less commuting time ( Oakman, Kinsman, Stuckey, Graham, & Weale, 2020 ), as well as challenges, such as intensified technical, psychological, and emotional work demands ( Chan, Shang, Brough, Wilkinson, & Lu, 2022 ). It is expected that this shift to remote and hybrid working will continue in the future, challenging health behaviors such as movement and dietary behaviors ( Peters, Dennerlein, Wagner, & Sorensen, 2022 ), which are typically embedded into structures related to work or school ( Brazendale et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%